2010
DOI: 10.1109/tmtt.2010.2076670
|View full text |Cite
|
Sign up to set email alerts
|

Data Transmission Using Differential Phase-Shift Keying on a 92 GHz Carrier

Abstract: Wireless data transmission with binary phase-shift keying modulation encoded on a 92 GHz carrier is achieved using photonic components. A high-speed photodiode is used to convert the doubly-modulated optical signal to a modulated millimeter-wave carrier. A W-band Mach-Zehnder interferometer with a one-bit time delay is used to directly detect the differential phase-shift keyed millimeter-wave wireless signal without the use of a local oscillator. Field tests with antennas separated by 890 m demonstrate the abi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 10 publications
0
12
0
Order By: Relevance
“…More advanced modulation formats in the W-band such as differential phase shift-keying (DPSK), binary/quadrature phase shift-keying (BPSK/QPSK) with data rates of 10 Gbit/s and 20 Gbit/s are reported in [6][7][8]. Most recently, 40 Gbit/s 16-level quadrature amplitude modulation (16-QAM) wireless transmission in the W-band is presented [9].…”
Section: Introductionmentioning
confidence: 99%
“…More advanced modulation formats in the W-band such as differential phase shift-keying (DPSK), binary/quadrature phase shift-keying (BPSK/QPSK) with data rates of 10 Gbit/s and 20 Gbit/s are reported in [6][7][8]. Most recently, 40 Gbit/s 16-level quadrature amplitude modulation (16-QAM) wireless transmission in the W-band is presented [9].…”
Section: Introductionmentioning
confidence: 99%
“…The W-band has much lower propagation loss and a broader transmission window compared with the 60 and 120 GHz bands, and has been specified as the window for outdoor 'gigabit' wireless data transmission in several countries [5]. Recently, a number of research groups have demonstrated high-performance photonic-wireless linking in this band [78][79][80]82,83]. In our recent work, we demonstrated errorfree 20 Gbit s -1 OOK wireless data transmission in the W-band using an NBUTC photodiode-based photonic transmitter-mixer [80].…”
Section: Photonic Millimeter-wave Wireless Linksmentioning
confidence: 99%
“…Using such a technique (envelope detection), 20 Gbit s -1 error-free wireless data transmission at a center frequency of 93 GHz has been demonstrated [80]. Comparison is made with the reported 16-QAM, OFDM or differential phase-shift keying modulation formats [82,83]. The OOK modulation formats, despite providing extremely high data transmission rates (>12.5 Gbit s -1 ) [6,80], incur serious problems with regard to the multi-path effect and occupy a larger bandwidth for the same desired data rate.…”
Section: Photonic Millimeter-wave Wireless Linksmentioning
confidence: 99%
“…The United States and Canada recently allocated the 90 GHz band and specified the technical criteria of the 90 GHz band for fixed point-to-point wireless communications. Recent studies presented systems and technologies for 40 GHz, 60 GHz and 70 GHz to 90 GHz band wireless communications [2]- [11]. In previous works, the frequency-division duplex (FDD) scheme [2], [7]- [9] or time-division duplex (TDD) scheme [3]- [4], [9] was used for full-duplex communication.…”
Section: Introductionmentioning
confidence: 99%